Electrically Tunable Scattering from Devitrite–Liquid Crystal Hybrid Devices. Issue 1 (18th October 2016) - Butt, Haider; Yetisen, Ali K.; Khan, Ammar A.; Knowles, Kevin M.; Qasim, Malik M.; Yun, Seok Hyun; Wilkinson, Timothy D.
Abstract : Devitrite is normally an unwanted crystalline impurity in the soda‐lime‐silica glass making process. Thin needles formed by heterogeneous nucleation of devitrite on the glass surface provide unique birefringence properties for potential applications in tunable optical devices. Here, devitrite and a liquid crystal are combined to create an electrically variable optical diffuser. The magnitude and scattering angle of the transmitted light propagating through the diffuser are tuned by varying the voltage between the graphene and indium tin oxide electrodes on either side of the liquid crystal. The threshold voltage to switch the transmitted light from a predominantly horizontal diffusion to a random order is 3.5 V. Angle‐resolved measurements show broad diffusion angles of transmitted light with a maximum deflection of ±60°. The dynamically tunable devitrite‐liquid crystal hybrid devices may advance the development of currently less viable technologies including beam shaping and automatic light transmission control. Abstract : The optical characteristics of devitrite and liquid crystal are integrated to fabricate an electrically variable optical diffuser. The magnitude and the transmission scattering angle of the device are tuned by changing the voltage between graphene and indium tin oxide electrodes to achieve optical diffusion up to ±60°.